The Competitiveness of Inbound Tourism in Lithuania in the Baltic Context - Petrilovskaja, Karolina; Miškinis, Algirdas (Ekonomika, 2007)
The purpose of the article is to evaluate the inbound tourism in Lithuania and its competitiveness in comparison with other Baltic States. The objectives are to evaluate the role of the tourism sector in Lithuanian economy, its potential, and by comparative analysis to identify its development prospects in the context of the other Baltic States. The competitiveness analysis of the Lithuanian tourism industry is based on secondary data, while research of the Lithuanian image relies on information collected using a questionnaire. Comparative analysis revealed that, despite the fact that the tourism sector in Lithuania develops very rapidly, it is still behind the level of Estonia which is the leading tourism nation in the Balties. The main reason for smaller numbers of tourists in Lithuania is a poorer access to Lithuania through airports or the Klaipėda port. The lack of cheap hotels and motels is another reason. To further develop the tourism sector in Lithuania, there is a need to introduce new tourism products - new routes for the groups, European level cultural, educational, sports and political events, countryside tourism. It is important to increase information and publicity on Lithuania and its famous places, traditions, history, people, - in other words, to create the Lithuanian tourism brand. The research of Lithuanian competitiveness and image has indicated the following shortcomings of the Lithuanian inbound tourism sector: the lack of cheap hotels and motels, the problem of tourists’ safety in the country, the lack of information about the country and its famous places, inadequate development of the Lithuanian transport sector. To enhance the competitiveness of the Lithuanian tourism industry, it is necessary to develop targeted public strategies supported by adequate financial resources.